2018
DOI: 10.1021/acs.jmedchem.8b00718
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Challenges in Docking Screens for GPCR Targets and Antitargets

Abstract: To investigate large library docking’s ability to find molecules with joint activity against on-targets and selectivity versus antitargets, the dopamine D2 and serotonin 5-HT2A receptors were targeted, seeking selectivity against the histamine H1 receptor. In a second campaign, κ-opioid receptor ligands were sought with selectivity versus the μ-opioid receptor. While hit rates ranged from 40% to 63% against the on-targets, they were just as good against the antitargets, even though the molecules were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 86 publications
(173 reference statements)
0
31
0
Order By: Relevance
“…Second, we showed that consideration of ensembles based on different templates can reduce bias towards certain ligand chemotypes, which can increase the diversity of hits from docking screens. Finally, as demonstrated by previous prospective studies [26,28], it will be essential to consider binding site flexibility if the aim of the screen is to identify selective ligands by docking to targets and antitargets. In such applications, a flexible representation of the receptor is crucial to ensure that predicted ligands do not bind to any accessible conformation of the antitarget.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we showed that consideration of ensembles based on different templates can reduce bias towards certain ligand chemotypes, which can increase the diversity of hits from docking screens. Finally, as demonstrated by previous prospective studies [26,28], it will be essential to consider binding site flexibility if the aim of the screen is to identify selective ligands by docking to targets and antitargets. In such applications, a flexible representation of the receptor is crucial to ensure that predicted ligands do not bind to any accessible conformation of the antitarget.…”
Section: Discussionmentioning
confidence: 99%
“…A model that displays high enrichment of known ligands is considered to be a good representative of the receptor structure and suitable for virtual screening. Despite the challenges involved in predicting the structures of GPCRligand complexes, several virtual screens against homology models have been successful [12,[25][26][27][28][29][30][31]. For example, Carlsson et al demonstrated that a high quality model of the D 3 dopamine receptor performed as well as a crystal structure in prospective molecular docking screens [29].…”
Section: Introductionmentioning
confidence: 99%
“…The recent determination of the MT 1 and MT 2 receptor crystal structures 13 , 14 afforded us the opportunity to seek new chemotypes with new functions, including MT 1 -selective ligands, by computational docking of an ultra-large make-on-demand library 15 , seeking molecules that complemented the main ligand binding (orthosteric) site of the receptor. Given the similar MT 1 and MT 2 sites, where 20 of 21 residues are identical, and the challenges of docking for selectivity 16 , we sought to prioritize new, high-ranking chemotypes from the docking screen, unrelated to known melatonin receptor ligands, expecting these to differentially interact with the two melatonin receptor types 17 19 .…”
Section: Summary Paragraphmentioning
confidence: 99%
“…For aminergic GPCRs, there has been some recent success in discovering the structural features responsible for polypharmacological activities 33 which comprises a series of 9 semi-conserved residues (Asp 3.32 , Ile/Val 3.33 ; Cys 3.36 , Thr 3.37 , Ala/Ser/Thr 5.46 , Trp 6.48 , Phe 6.51 , Phe 6.52 , EL2Val/Ile/Leu). Although in theory structure-guided approaches should be helpful for the discovery and design of polypharmacological drugs, to date, this has not been entirely successful 117,118…”
Section: Challenges and Opportunities For Structure-guided Drug Desigmentioning
confidence: 99%